Chemical composition and nutritive values of cassava pulp for cattle. (29th May 2018) - Keaokliang, Ornvimol; Kawashima, Tomoyuki; Angthong, Wanna; Suzuki, Tomoyuki; Narmseelee, Ramphrai
Abstract: We evaluated the chemical compositions of cassava pulp samples produced by four cassava starch factories at different locations in northeast Thailand and the metabolizable energy (ME) of the cassava pulp for cattle. There were significant differences in the P (0.03% ± 0.02%) and K (0.36% ± 0.2%) contents of the samples from different factories ( p  <   .05). Moreover, we found interactions between factory and season in the neutral detergent fiber (36.02% ± 8.8%) and nonfibrous carbohydrate contents (59.33% ± 9.1%) ( p  <   .05). For the evaluation of ME, a crossover‐design experiment with four cattle maintained in each of two groups was conducted. There were two dietary treatments at a maintenance level of 1.27% body weight: (1) a control diet, and (2) a cassava pulp diet, containing the control diet at 70.2% and cassava pulp at 29.8% (dry matter [DM] basis). Feeding cassava pulp did not affect energy intake, energy loss, heat production, energy utilization efficiency (except for the urine‐to‐gross energy ratio), methane production, fecal N, or nutrient digestibility (except for crude protein digestibility). The total digestible nutrients, digestible energy, and ME contents of cassava pulp were 74.4%, 12.9 MJ/kg DM, and 11.3 MJ/kg DM, respectively.